(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2024)
Malnutrition is a dysfunction between energy intake and the body’s nutritional requirements, due to inappropriate nutrition. Children are the most affected population, so it is of great importance to intervene in the social determinants due to the irreversible biological sequelae that this event triggers. This research was conducted under a quantitative cross-sectional study, the sample size was 117 families each representing a minor and of the total number of participants each represented a family nucleus: The population were residents of the communes 13, 14, 15 and 21 of the city of Santiago de Cali. Data was collected using the Latin American and Caribbean Food Security Scale (ELCSA) questionnaire. As a result, the following results were obtained in terms of food security: 37 households were food secure (31,6%), 46 households were mildly food insecure (39,3%), 18 households were moderately food insecure (15,4%) and 16 households were severely food insecure (13,7%); 80% of the children were under the care of the mother, who did the household chores; the average age of the adults surveyed was 28,6 years; only 44% had completed secondary education, and in 48,7% of the households the economic income was valued at less than 1.000.000COP. The predominant level of food security was security; however, among the members of the household there was a youngest member with malnutrition, a situation that allowed us to identify that the food did not meet the nutritional requirements for the proper development of the infant.